2007
DOI: 10.2174/156720207779940707
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Administration Modulates Neural Stem Cell Survival and Serotoninergic Differentiation Through Bcl-2

Abstract: The hippocampus has long been associated with learning, memory, and modulation of emotional responses. Previous studies demonstrated that stress-induced loss of hippocampal neurons may contribute to the pathogenesis of depression. The recent observations supported that antidepressant drugs increase the production of serotoninergic neurotransmitter and they play a critical role in the initiation of neurogenesis in the hippocampus. In order to explore the possible new mechanism of the treatment of depression, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 32 publications
1
24
1
Order By: Relevance
“…Our findings differ from previous studies, which argued that cell proliferation occurred after two or three weeks of FLX treatment in vivo or in vitro (Kodama et al, 2004;Malberg and Duman, 2003;Manev et al, 2001;Santarelli et al, 2003). The current study, however, produced results similar to those of Chen et al,2007), who observed cell proliferation under in vitro conditions after seven days, though they used different cell type and culture conditions. It is highly likely that the discrepancies observed are due to differences in the experimental design -i.e., in vivo or in vitro tests.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings differ from previous studies, which argued that cell proliferation occurred after two or three weeks of FLX treatment in vivo or in vitro (Kodama et al, 2004;Malberg and Duman, 2003;Manev et al, 2001;Santarelli et al, 2003). The current study, however, produced results similar to those of Chen et al,2007), who observed cell proliferation under in vitro conditions after seven days, though they used different cell type and culture conditions. It is highly likely that the discrepancies observed are due to differences in the experimental design -i.e., in vivo or in vitro tests.…”
Section: Discussioncontrasting
confidence: 99%
“…This indicates that although induced apoptosis is usually associated with changes in the amount of apoptotic gene transcripts, induced without changes in the transcript level of these genes probably due to posttranscriptional induction/regulation of the pathway. Previous studies examined the effects of FLX on apoptosis with different types of cell, such as adult neurons, hepatocytes, lymphoma cells, and neuroblastoma cells (Chen et al, 2007;Chiou et al, 2006;Koch et al, 2003;Lee et al, 2001;Levkovitz et al, 2005;Nahon et al, 2005;Serafeim et al, 2003). However, these studies used nonhuman CNS cells and animal models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 An strong upregulation of neurogenesis in association with an upregulation of Bcl-2 expression in the dentate gyrus was measured as well in nonhuman primates receiving electroconvulsive therapy (ECT), another potent therapeutic intervention used against depression. 43 Therefore, an increase of Bcl-2 expression levels might be a major component of the antidepressant activity.…”
mentioning
confidence: 99%
“…Fluoxetine, one of the most used selective serotonin reuptake inhibitors, induces proliferation of rat hypothalamic neural progenitors in vitro 7,8 .…”
Section: Introductionmentioning
confidence: 99%